Isolation and characterization of carcinogenic chromium reducing bacillus pumilus from tannery effluent of Hazaribag area - Ferdushi, Mahia (BRAC Univeristy, 2018)
This project report is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2017.